Embryo Donation or Embryo Adoption? Practice and Policy in the New Zealand Context. (10th March 2017) - Goedeke, Sonja; Daniels, Ken R.
ABSTRACT: Embryo donation (ED) is the donation by a couple who have surplus embryos following IVF to another infertile person/s. There has been much debate as to whether ED can be understood as akin to gamete donation or as adoption, as these viewpoints evoke different health and welfare concerns and implications for the various parties. In this article, we discuss the legislative frameworks, policy guidelines, and practice of ED in New Zealand in comparison with those of other countries. We demonstrate how New Zealand's ED requirements and practices may invite conceptualizations of ED as adoption, as there are similar practices and procedures aimed at promoting child welfare: ED must be approved by an overseeing body, donors select recipients for their embryos, donor: recipient 'matching' is encouraged, and a joint donor: recipient meeting explores the needs and rights of children to have access to genetic knowledge, feelings related to parenting and relinquishment, and information-sharing and contact expectations. We discuss how research of donor and recipient experiences suggests that the adoption metaphor may provide a model of family-building from which to make sense of ED. However, the metaphor also highlights longer- term child welfare concerns and raises policy issues in relation to both ED as well as open adoption practices, both locally and internationally.